ChemInform Abstract: Bentonite Clay: An Efficient Catalyst for the Synthesis of 2‐Substituted Benzimidazoles. Issue 1 (17th December 2015) - Cardozo, Victor A.; Sanchez‐Obregon, Ruben; Salgado‐Zamora, Hector; Jimenez‐Juarez, Rogelio
Abstract: The procedure has several advantages, including short reaction times, large‐scale preparations, easy isolation of the products (III), and good to excellent yields.